Determinasi Keberhasilan Prestasi Atlet Para-Cycling Indonesia dalam Perspektif Integrasi LTAD pada Asian Para Games Hangzhou 2023 - Rizan Setyo Nugroho; Nuruddin Priya Budi Santoso; Joko Sulistyono; Teguh Santosa; Shodiq Hutomono; Bagus Kuncoro (Bulletin of Community Engagement, 2026)
Performance sports for people with disabilities in Indonesia have undergone significant development alongside a paradigmatic shift toward a human rights-based approach, positioning para-athletes as subjects with the potential to achieve elite performance. One discipline demonstrating such progress is para-cycling, which demands the integration of physical and mental capabilities, supported by a structured development system. Nevertheless, athletic success is not dictated by physical attributes alone; rather, it is influenced by a complex interaction of various internal and external factors. This study aims to analyze the factors influencing the success of Indonesian para-cycling athletes in achieving international distinction. A descriptive qualitative method with a case study approach was employed, utilizing in-depth interviews, observations, and documentation involving athletes, coaches, and high-performance administrators. Data were processed using thematic analysis to identify relational patterns between factors. The results indicate that athletic success—specifically the attainment of gold medals in international arenas—is the result of a hierarchical and causal process. Internal factors, namely innate potential and mental toughness, serve as the primary determinants that initiate the development process. External factors, such as coaching roles, facilities and infrastructure, government support, and the implementation of Long-Term Athlete Development (LTAD), function as supporting elements that reinforce performance. Furthermore, prior experience in other sporting disciplines contributes through a skill transfer mechanism that accelerates athlete adaptation. This research underscores that the success of para-cycling athletes is not merely a matter of physical capacity but is deeply dependent on mental strength as the core foundation, supported by an integrated sports development system